(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2022)
The basic purpose of bitumen of a mineral powder as be completed of bitumen is to translate volumetric bitumen in a film status. In such status the viscosity and durability of bitumen raises. The important value has that circumstance, that the application of the activated polymeric powders essentially reduces the charge of bitumen and completed.